Divine Temporality and Providential Bodgery - Mullins, R. T. (TheoLogica, 2021)
In contemporary debates, one is presented with temporal and timeless conceptions of divine eternality. Each conception is said to have various consequences for understanding divine perfection and providence. In this paper, I shall consider a pair of arguments against divine temporality that suggest that a temporal God could potentially make mistakes, thus making the temporal God less than perfect. I shall develop these objections, and discuss various ways for the temporalist to reply.